2019
DOI: 10.9778/cmajo.20180028
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk and breast screening for trans people: an integration of 3 systematic reviews

Abstract: rans" is an umbrella term for people with diverse gender identities and expressions that differ from stereotypical gender norms. 1,2 Recent estimates suggest that there were approximately 200 000 trans people in Canada in 2016. 3 Many trans people seek gender-affirming medical procedures or cross-sex hormone (CSH) therapy, or both, to align their physical appearance with their sense of self. 4 Cross-sex hormone therapy refers to the use of exogenous sex hormones that are opposite to those of a person's natal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…A second major finding was that only one-third of respondents had knowledge of mammographic screening recommendations for transgender women. Expert guidance for transgender breast cancer screening varies among organizations [5]; an accepted approach is summarized in Table 1. This guidance is informed by the experience of one large European study that demonstrated a 46-fold elevated risk for breast cancer in transgender women treated with estrogen compared with cisgender men, as well as a lower risk for breast cancer in transgender men compared with cisgender women [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A second major finding was that only one-third of respondents had knowledge of mammographic screening recommendations for transgender women. Expert guidance for transgender breast cancer screening varies among organizations [5]; an accepted approach is summarized in Table 1. This guidance is informed by the experience of one large European study that demonstrated a 46-fold elevated risk for breast cancer in transgender women treated with estrogen compared with cisgender men, as well as a lower risk for breast cancer in transgender men compared with cisgender women [25].…”
Section: Discussionmentioning
confidence: 99%
“…Definitions relevant to the survey (ie, sex, gender identity, transgender, transition, cisgender, sexual orientation, and the "two-step" method for classifying sex) on the basis of relevant literature were provided to reduce confusion about terminology (Table 2) [10,15]. The "two-step" method was developed as a reliable means of accurately identifying Note: Recommendations are derived from a meta-analysis [5] and expert opinion [6][7][8].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As with cis-gendered individuals--particularly women--due to breast cancer risks faced by transgender people, breast cancer screening is widely recommended (Meggetto et al, 2019). There are some suggestions that breast cancer screening guidelines (in the Netherlands) for cisgender people are adequate for transgender people using hormone treatment (de Blok et al, 2019).…”
Section: Backg Rou N Dmentioning
confidence: 99%